Pengaruh Aromaterapi Lavender Terhadap Tingkat Kecemasan Pada Ibu Hamil Trimester 3 Di Wilayah Pucangsawit - Kusuma, Jane Nathania; Hutari Pujiasuti; Ajeng Maharani Pratiwi (Jurnal Medicare, 2025)
During pregnancy, a woman's body undergoes biological changes. Anxiety is a condition in which behavioral patterns are manifested by emotional states caused by unpleasant thoughts and feelings. These emotional states are risk factors for developing psychological disorders. The purpose of this study was to determine whether there is an effect of lavender aromatherapy on anxiety levels in third-trimester pregnant women in the Pucangsawit region. The method used in this study was quantitative research, employing a pre-experimental design with a One Group Pretest-Posttest Design. The study sample included 30 pregnant women in the Pucangsawit region. Data analysis utilized the Wilcoxon Signed Rank Test. Based on the results of the Wilcoxon Signed Rank Test, a p-value of 0.001 < 0.05 was obtained. The conclusion drawn is that there is an effect of lavender aromatherapy on anxiety levels in third-trimester pregnant women.